PENERAPAN AGRARISCHE WET (UNDANG-UNDANG AGRAIA) 1870: PERIODE AWAL SWASTANISASI PERKEBUNAN DI PULAU JAWA - M Masyrullahushomad; S Sudrajat (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
The development of plantations in Indonesia is divided into two phases. The first phase is called the state plantation phase (1830-1870). Meanwhile, the second phase is the private plantation phase, the phase after the implementation of the Wet Agrarische 1870 (Agrarian Law). The Wet 1870 Agrarische became the formal juridical foundation for the entry of non-government private investment in the plantation industry in the Indies. The direct impact of the implementation of the Wet Agrarische 1870 was the increasing intensity of the number of plantation commodity exports and the increasing breadth of large plantation land in the Dutch East Indies, especially in Java.